Pengaruh Employee Well-Being terhadap Kinerja Guru di Era Bani - Dewi Fitrotus Sa’diyah; Zujajatul ‘ilmi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This research is motivated by the increasing complexity of professional demands on teachers in the digital era, which impacts psychological, emotional, and spiritual well-being. An imbalance in employee well-being has the potential to reduce teacher performance and the quality of learning. On the other hand, conventional approaches to human resource management tend not to comprehensively integrate the spiritual dimension, particularly from an Islamic perspective. This study aims to analyze the influence of employee well-being on teacher performance and to examine the role of spiritual well-being as a reinforcing factor in this relationship. The research employs a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 120 teachers and analyzed using multiple linear regression. The results show that employee well-being has a positive and significant effect on teacher performance. Furthermore, the spiritual well-being dimension is proven to strengthen the relationship between well-being and performance. These findings indicate that integrating psychological and spiritual aspects into educational human resource management is an important strategy for improving teacher performance sustainably in the digital era